Facile method to reduce surface defects and trap densities in perovskite photovoltaics - Han, Guifang (2020)
Owing to improvements in film morphology, crystallization process optimization, and compositional design, the power conversion efficiency of perovskite solar cells has increased from 3.8 to 22.1% in a period of 5 years. Nearly defect-free crystalline films and slow recombination rates enable polycrystalline perovskite to boast efficiencies comparable to those of multicrystalline silicon solar cells. However, volatile low melting point components and antisolvent treatments essential for the processing of dense and smooth films often lead to surface defects that hamper charge extraction. In this study, we investigate methylammonium bromide (MABr) surface treatments on perovskite films to compensate for the loss of volatile cation during the annealing process for surface defect passivation, grain growth, and a bromide-rich top layer. This facile method did not change the phase or bandgap of perovskite films yet resulted in a significant increase in the open circuit voltages of devices. The devices with 10 mM MABr treatment show 2% improvement in absolute power conversion efficiency over the control sample.